2014
DOI: 10.2139/ssrn.2553129
|View full text |Cite
|
Sign up to set email alerts
|

Voting for Direct Democracy: Evidence from a Unique Popular Initiative in Bavaria

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We also checked for the effect of age since several studies showed that younger people favor direct democracy more strongly than older citizens (Dalton et al 2001;Jeydel & Steel 2002;Donovan & Karp 2006;Rose & Borz 2013;Arnold et al 2014).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also checked for the effect of age since several studies showed that younger people favor direct democracy more strongly than older citizens (Dalton et al 2001;Jeydel & Steel 2002;Donovan & Karp 2006;Rose & Borz 2013;Arnold et al 2014).…”
Section: Control Variablesmentioning
confidence: 99%
“…This approach is in line with several empirical studies in the field. For example, there is a difference within the representative system between government and parliament (among other institutions such as parties) (Christensen, 2017) or political dissatisfaction can be differentiated between representative democracy in general and institutions of representative democracy (Arnold et al, 2014).…”
Section: State Of the Art And Hypothesesmentioning
confidence: 99%